Mitigation of heat stress effects on laying hens' performances, egg quality, and some blood parameters by adding dietary zinc-enriched yeasts, parsley, and their combination - Cornescu, Gabriela Maria; Panaite, Tatiana Dumitra; Untea, Arabela Elena; Varzaru, Iulia; Saracila, Mihaela; Dumitru, Mihaela; Vlaicu, Petru Alexandru; Gavris, Teodor (Frontiers in Veterinary Science, 2023)
The study aimed to experiment natural, handy and efficient nutritional solutions to prevent and mitigate negative effects caused by environmental heat stress and to be applied to large-scale laying hen industry. A three weeks trial was conducted on 128 laying hens TETRA-SL LL (50 weeks of age) housed in 8 cages/group, 4 laying hens/cage, 32 laying hens/group, under heat stress conditions (34±1°C). The basal diet on corn and soybean meal was formulated to be isocaloric and isonitrogenic. Compared to Control group diet (C), experimental groups: E1 included 1% Zn-enriched yeast; E2 included 2% parsley and E3 included 1% Zn-enriched yeast combined with 2% parsley with the objective of mitigating heat stress effects. A statistically significant (p < 0.05) average egg weight was noticed on E2 and E3 compared to Control group, and also during the 1st week compared to the 2nd and the 3rd experimental weeks. Average daily feed intake values were highly significant (p < 0.001) on E3 group compared to Control, E1, E2, and on the 2rd week compared to the 3nd experimental week (p < 0.021). Feed conversion rate was highly significant (p < 0.001) during the 2rd and the 3nd experimental weeks compared to the 1st week. The average daily egg production was highly significant (p < 0.001) within 1st week compared to the 2nd and 3rd weeks. A highly significant (p < 0.001) yolk coloration was noticed on E2 and E3 groups. The malondialdehyde (MDA) concentration decreased significantly (p < 0.05) to all experimental groups compared to Control group during the 14th and 28th days of storage.